PEMETAAN SOSIAL-POLITIK KELOMPOK ETNIK CINA DI INDONESIA - Amri Marzali (Masyarakat Indonesia, 2011)
This article presents a brief and comprehensive picture of the sociocultural lifeof the Indonesian Chinese society in Indonesia. The paper covers historical,demographic, legal, economic, political, and cultural aspects. It aims toupdate the data and information given by Mackie and Coppel (1976). Someobservations are derived based on feld research on Chinese-Pribumi relationsin several cities in Indonesia, such as Jakarta, Solo and Tangerang.The paper compiles several dispersed sources of information to give a briefcomprehension of the sociocultural life of the Indonesian Chinese society inIndonesia.